Only the brave : a novel [compact disc, unabridged] - Steel, Danielle (Recorded Books, Llc, 2024)
In Nazi-era Berlin, Sophia Alexander shoulders immense responsibility after her mother's death, managing her family and aiding the resistance. Amidst Hitler's tyranny, Sophia assists in her sister's daring escape from Germany, endures personal losses, and joins the Sisters of Mercy. Despite danger, she persists in rescuing Jewish children, defying surveillance and persecution, determined to help those in need, even at the risk of her freedom.